Effect of childhood proximity to lead mining on late life cognition - Mark Lee; Haena Lee; John Robert Warren; Pamela Herd (Elsevier, 2022)
Introduction: Lead exposure negatively affects cognitive functioning among children. However, there is limited evidence about whether exposure to lead in early life impairs later life cognitive functioning. Methods: Participants in the prospective Wisconsin Longitudinal Study cohort (N = 8583) were linked to the 1940 Census, which was taken when they were young children. We estimated the effect of living near a lead mine in childhood on late life memory/attention and language/executive function in 2004 (mean age 64) and 2011 (mean age 71). Results: Lead-exposed children had significantly steeper memory/attention decline between 2004 and 2011 and worse language/executive function at baseline in late life. These long-term effects of lead were not mediated through adolescent IQ or late life SES and health factors. Discussion: Proximity to lead mining in childhood had long-term effects on late life memory/attention decline and language/executive function, reflecting a possible latent influence of lead exposure. More research is needed to understand behavioral and biological pathways underlying this relationship.